Evaluation of Mast Cells in Oral Potentially Malignant Disorders and Oral Squamous Cell Carcinoma - Ashish Shrestha; Shashi Keshwar; Toniya Raut (International Journal of Dentistry)
Background. Oral squamous cell carcinoma (OSCC) and oral potentially malignant disorders (OPMDs) are epithelial-derived pathologies which share inflammation as a common initial pathogenic-inducing state. Mast cell is a key immune modulating cell which is primarily involved in initiation and propagation of inflammation. The role of mast cell in OPMDs and OSCC has been an established fact; however, its definitive pathogenic correlation is still under study. The objective of the study was to evaluate the number of mast cell in OPMDs and OSCC using special stain correlating its probable role as a promoter or retarder of OSCC. Materials and Methods. Forty-five archival histopathologically confirmed cases each of OPMD and OSCC were studied for mast cells using toluidine blue and Alcian blue-safranin stain and compared with 10 normal oral mucosal tissues. Comparisons between the mast cells count was also performed between the two special stains. Results. Among 100 cases, 67% were males and 33% were females. The mean age was 41.68 ± 13.39; 55.06 ± 12.55; and 18.4 ± 2.54 years for OPMDs, OSCC, and normal, respectively. A statistically significant increase in mast cells among OPMDs (9.88 ± 7.9) and OSCC (6.711 ± 3.94) was observed compared to normal oral mucosa. The mast cell count reduced among OSCC in comparison to OPMDs which was significant as well. The mean mast cell count for Alcian blue-safranin stain was higher than toluidine blue stain. Conclusion. There is a decrease in mean mast cell count from OPMDs to OSCC which is suggestive of protective role of mast cell. Proper quantification of mast cells using specific stains can guide to define prognosis in oral potentially malignant disorders and oral cancer.